SOSIALISASI DAN PRAKTIK PEMBUATAN SABUN CAIR MENGGUNAKAN ESENSTIAL OIL PADA MASYARAKAT DESA TAMBAK REJO BENGKULU UTARA - Krisandini, Triana; Handayani, Dewi; Elvia, Rina (Universitas Bengkulu, 2025)
Community service is a tridharma activity of higher education that must be carried out by all lecturers. The theme of this community service activity is Socialization and Practice of Making Liquid Soap Using Essential Oils in the Tambak Rejo Village Community, North Bengkulu. Soap is a primary material used in everyday life by the community in general. Making soap cannot be separated from the application of chemical concepts. In this community service activity, the community is given information and practice of making simple and easy-to-do soap. This activity was carried out in the Tambk Rejo Village Meeting Room, North Bengkulu. The expected output of this activity is in the form of documentation and publication articles from this community service activity. The expected result is an increase in understanding of making economical soap for everyday life. Keywords: Liquid Soap; Essential Oil; Chemistry Practice